The complete chloroplast genome sequence of the medicinal plant Elsholtzia rugulosa Hemsl (Labiatae). Issue 2 (2nd April 2020) - Zhang, Lansheng; Tao, Aien; Zhao, Feiya
Abstract: Elsholtzia rugulosa is a medicinal plant commonly used in southwest of China. In this study, we sequenced the complete chloroplast (cp) genome sequence of E. rugulosa to investigate its phylogenetic relationship in the family Labiatae. The chloroplast genome of E. rugulosa was 151, 952 bp in length with 37.9% overall GC content, including a large single copy (LSC) region of 83, 056 bp, a small single copy (SSC) region of 17, 526 bp, and a pair of inverted repeats (IRs) of 25, 685 bp. The cp genome contained 113 genes, including 80 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. The phylogenetic analysis indicated Elsholtzia was closely related to Perilla .